Autoritarism or democracy - Aigneren, Miguel (La Sociología en sus Escenarios, 2009)
Abstract It is clear that the only point of consensus within the ruling coalition regards the necessity to maintain the military regime for an extended period of time, longer even than the officially designated period of ’transition’, which, in accordance with the 1980 political constitution, should conclude in 19891. This consensus tends to dissolve when a political model to succeed the military regime is discussed. Some sectors believe that it is necessary to maintain the military regime indefinite since their own positions of power and influence depend upon the very existence of the political-military model. Finally, the plan proposed by the hegemonies block, is a political system based upon an authoritarian regime with restricted political representation, a very strong mechanism for political exclusion, which would relegate to the armed forces the role of arbiters Resumen Es evidente que el único punto de consenso en el seno de la coalición gobernante, es la necesidad de mantener el régimen militar durante un largo período de tiempo, más largo incluso que el designado oficialmente período de ’transición’, que, de conformidad con la Constitución política de 1980, Debería concluir en 1989. Este consenso tiende a disolver cuando un modelo político para tener éxito el régimen militar se discute. Algunos sectores creen que es necesario mantener el régimen militar indefinida desde sus propias posiciones de poder e influencia dependen de la existencia misma del modelo político-militar. Por último, el plan propuesto por el bloque de hegemonías, es un sistema político basado en un régimen autoritario con restricciones de la representación política, un fuerte mecanismo de la exclusión política, que relegan a las fuerzas armadas el papel de árbitros